Exploratory Analysis of Energy Use Across Building Types and Geographic Regions in the United States - Sohn, Michael D.; Dunn, Laurel N. (Frontiers in Built Environment, 2019)
Collecting energy use data is becoming common practice in the buildings sector. Current applications include understanding regional energy flows in the building stock, and tracking energy performance of individual buildings. Beyond these, research and commercial applications of building energy data are as yet unexplored. Research is needed to provide insight into the data being collected, to identify appropriate applications of these data, and opportunities to improve data collection efforts. To that end, we present an exploratory analysis of the existing public large-scale building energy datasets, focusing on the two largest datasets: the Commercial Building Energy Consumption Survey and the Building Performance Database. We provide backgound information on both datasets, present an overview of the detail and sparsity of information in each, and report on the relationships we observe between data fields included in the two datasets, and compare our findings with results from the literature. We discuss how these results could be applied to support energy efficiency investments, and opportunities to improve data collection efforts to ensure that the data collected are adequate to provide insight into building energy consumption and support novel applications of building energy data.